Arabic Reading and Writing at Education Based on the Common European Framework of Reference (CEFR) - Sa'idah, Umm; Budiyanto, Muhammad Arief; Tahir, Saidna Zulfiqar Bin (Yayasan Vifada Cendikia Indonesia, 2024)
Learning is a combination formed from several elements, including materials, which can influence the achievement of learning objectives. Material elements include: textbooks, so that research on the design of Arabic reading and writing materials for beginners based on the Common European Framework of Reference (CEFR) is worth doing. This study aims to determine: (1). Design of Arabic reading and writing materials for beginners based on CEFR at MTS Khoiru Ummah, Central Maluku Regency. (2). Supporting and inhibiting factors in designing Arabic reading and writing materials for beginners based on CEFR at MTS Khoiru Ummah, Central Maluku Regency. This research is a development research. Research and development include one of the methods to obtain certain new results, models, methods, strategies, ways, designs, or steps with descriptions and development of results and trials to obtain maximum results. Learning reading and writing skills continues to experience curriculum development from time to time. CEFR theory has contributed to the development of the curriculum design for learning these two Arabic language skills. This CEFR-based curriculum is designed by determining the limits of learning objectives at levels A1 and A2. CEFR has 6 levels, the lowest A1 and the highest C2 in the order of A1, A2, B1, B2, C1, and C2. Levels A1 and A2 are designed for beginners in every foreign language learning based on this theory. At the beginner level, students are able to distinguish the sounds of hijaiyah letters, read and write words that are heard and seen, write and read simple phrases and sentences found around them well. Teaching materials are presented in the form of a communicative approach to make students more active and participate in the learning process by using modern learning media either in the form of materials or learning applications that support the achievement of goals. While the evaluation is presented by paying attention to the differences in students' intellectual abilities. Namely starting from easy questions then increasing in difficulty according to level. So that the curriculum for reading and writing language is presented in gradual teaching materials with familiar themes and following the development of the era and the environment of the students. Supporting and inhibiting factors in designing Arabic reading and writing materials based on CEFR at MTs Khoiru Ummah, Central Maluku Regency. a. Supporting Factors, 1) There is a curriculum used by MTs based on the 2013 curriculum for junior high school/MTs level and will implement the Merdeka curriculum at MTs. 2) Teaching staff in accordance with their fields, 3) Textbooks used. The school facilities and environment are very supportive in learning Arabic for beginners because students are required to be in the dormitory. b. Inhibiting Factors, 1) The level of student ability was not identified at the time of input or at the time of registration and entrance exams for MTs..2) The teaching materials in the textbooks used do not focus on reading and writing lessons, making it difficult for students to master Arabic reading and writing skills..